Maximizing Lifetime of Three-Dimensional Corona-Based Wireless Sensor Networks - Changqing Xia; Nan Guan; Qingxu Deng; Wang Yi (International Journal of Distributed Sensor Networks, 2014)
In a wireless sensor network (WSN), the energy of nodes closer to the sink node is usually exhausted sooner than others. This is known as the energy hole problem, which heavily affects the lifetime of the network. In this work, we study the lifetime maximization problem of a three-dimensional corona-based WSN with uniformly distributed sensor nodes and data transmission workload. We first derive the optimal configuration of the first layer of the corona to maximize the lifetime of the network. Then, we propose two strategies to configure nodes outside the first layer: the equal energy strategy (EES) which minimizes the number of hops to transmit data from sensor nodes to the sink and the local optimal energy (LOE) which stands for the fact that under this strategy each individual layer reaches its minimal energy consumption. Furthermore, the optimal equal distance strategy (OEDS) which is a simple deployment strategy was proposed to prolong the lifetime of the network by optimizing layer number k .